Power, government, and territory: analysis of Bagua conflict, Peru - Dolorier, Gabriela (2013)
Analyzing socioenvironmental conflicts dealing with primary resources is especially necessary to understand the context that explains the conceptions, uses, and governments of territories. This paper presents a diagnosis of the Bagua Conflict, which faced the Peruvian government with the Amazonian indigenous communities, through the Legislative Decrees present in the origin of the mobilizations, and also through the different ways to understand and use the territory. These analyses lead us to propose the construction of spaces for dialogue, participation, and, then, for the recognition of differences.